Analysis Figuratife Language Used In Dylan Thomas’s Selected Poems - Beby Damayanti Azrin; Syahrul Ramadhan (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This research was created to determine figurative language according to theory (Keraf, 2007) in several selected poems by Dylan Thomas. This research includes qualitative research with an object approach through qualitative methods to analyze 3 poems by Dyland Thomas namely, Do Not Go Gantle Into That Good Night, Love in The Asylum, and Clown in The Moon. The techniques used in data analysis are reading, finding, understanding, identifying and making conclusions from each poem by Dyland Thomas which is analyzed. The results of this research show that figurative language in this selected poem is eleven repetitions, four symbols, four similes, two hyperboles, one personification, and one oxymoron. So, it can be concluded that this selection of poems by Dyland Thomas is dominated by Repetition.